The Reasons behind Customer’s Resistance to Using Internet Banking - Means-end Approach a Study in Ho Chi Minh City - Xuan, Le Thi Thanh; Tien, Do Thi Thuy; Tuyet, Tran Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 3, 2018)
Internet banking is believed to bring numerous benefits to customers and banks themselves and is provided by most of the banks in Vietnam, but the number of users is still limited. This study therefore aims to investigate why Vietnamese users are resistant to using the Internet banking service. The study is based on Means-End Chain theory (MEC) and uses laddering interviews to collect data. The data from a sample of seventy-one respondents is analysed by employing the Association Pattern Technique (APT) and is then demonstrated on a Hierarchical Value Map (HVM). The research findings show that there are six attributes, leading to five consequences that give impact on Unsafety and Inconvenience as two crucial values which prevent customers from using the Internet banking service. Some recommendations are proposed accordingly to improve the Internet banking usage.